Application of ray-tracing to interpreting beam prints from fibre laser cutting - Alotaibi, M.; Atiyah, H.; MacKenzie, R.C.I.; Voisey, K.T. (Old City Publishing, 2017)
2D ray-tracing has been used to investigate the influence of inclined cutting front and the cutting edge on the exiting, surplus, laser beam while cutting 6 mm mild steel with a fibre laser, wavelength = 1070 nm. The ray-tracing model, which assumed a Gaussian beam, has investigated the distribution of this surplus beam as a function of kerf wall inclination angle. Multiple reflections are shown to broaden the spatial distribution of the surplus beam. Dross and kerf wall roughness also broaden the spatial distribution of the surplus beam. Comparison of an experimentally obtained beam print from the surplus beam for 1.07 µm fibre laser cutting of 6 mm stainless steel with modelled results allows inclination of the cut front to be estimated. The experimentally obtained beam print has features consistent with roughness/dross induced beam broadening.